Evaluation of a novel classification system to predict local recurrence in sarcoma patients undergoing hemipelvectomy with iliosacral resection. (1st February 2022) - Gosheger, Georg; Ahrens, Helmut; Dreher, Philipp; Schneider, Kristian N.; Deventer, Niklas; Budny, Tymoteusz; Heitkötter, Birthe; Schulze, Martin; Theil, Christoph
Abstract : Aims: Iliosacral sarcoma resections have been shown to have high rates of local recurrence (LR) and poor overall survival. There is also no universal classification for the resection of pelvic sarcomas invading the sacrum. This study proposes a novel classification system and analyzes the survival and risk of recurrence, when using this system. Methods: This is a retrospective analysis of 151 patients (with median follow-up in survivors of 44 months (interquartile range 12 to 77)) who underwent hemipelvectomy with iliosacral resection at a single centre between 2007 and 2019. The proposed classification differentiates the extent of iliosacral resection and defines types S1 to S6 (S1 resection medial and parallel to the sacroiliac joint, S2 resection through the ipsilateral sacral lateral mass to the neuroforamina, S3 resection through the ipsilateral neuroforamina, S4 resection through ipsilateral the spinal canal, and S5 and S6 contralateral sacral resections). Descriptive statistics and the chi-squared test were used for categorical variables, and the Kaplan-Meier survival analysis were performed. Results: Resections were S1 in 25/151 patients (17%), S2 in 70/151 (46%), S3 in 33/151 (22%), S4 in 77/151 (11%), S5 in 4/151 (3%), and S6 in 2/151 (1%). An internal hemipelvectomy was performed in 113/151 patients (75%), and 38/151 patients (25%) had an external hemipelvectomy. The predominant types of sarcoma were high-grade osteosarcoma in 48/151 patients (32%), chondrosarcoma in 41/151 (27%), Ewing sarcoma in 33/151 (22%), pleomorphic sarcoma in 17/151 (11%), and others in 2/151 (8%). LR was found in 24/151 patients (15%) with S3, S5, with S6 resections showing the highest rate of LR (p = 0.038). Overall, 19/151 patients (16%) had evidence of metastastic disease at the time of surgery and these patients showed poorer survival when compared to patients with no metastasis. Conclusion: The proposed classification can help to report and compare different surgical and reconstructive approaches in these difficult cases who are still have a considerable risk of LR. Cite this article: Bone Joint J 2022;104-B(2):290–296.